Diagnosis and Surgical Treatment of Epilepsy - Warren W. Boling (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Epilepsy is a common neurological disease that can affect all ages. Although the majority of people with epilepsy can have excellent seizure control with medication, about 30% will fail anti-epileptic drugs. For those with medically intractable epilepsy, recurrent seizures lead to elevated mortality and injury risks, and the seizures themselves are socially disabling. Fortunately, for many people with intractable epilepsy, epilepsy can be cured or seizures better controlled with surgery. Localization of the seizure focus followed by surgical resection provide the best opportunities to cure epilepsy. Having a better understanding of the neuro-anatomy and physiology of epilepsy improves our ability to define the epileptic network and effectively treat epilepsy. Minimal access surgical approaches result in more rapid recovery from surgery, less pain, and more satisfied patients. For individuals without an opportunity to cure their epilepsy, new and emerging technologies can improve their quality of life by preventing injuries and reducing seizure frequency and severity. This Special Issue will highlight advances in the diagnosis and surgical treatment of epilepsy, including imaging and electroencephalography (EEG) approaches to defining the epileptic focus, understanding the epileptic network, and characterizing the anatomical substrate of epilepsy.